Intrahepatic Cholangiocarcinoma Skin Metastasis in a Patient with Hidradenitis Suppurativa: A Rare Entity - Ali Y Fakhreddine; Theresa Yang; Guanghong Liao; Bahman Chavoshan (Global Journal of Rare Diseases - Peertechz Publications, 2020)
We present a challenging diagnosis of disseminated intrahepatic cholangiocarcinoma presenting with perineal cutaneous masses in a young African American male with known hidradenitis suppurativa. The patient was a 39-year-old male who presented to the emergency department with difficulty walking due to severe gluteal swelling and pain. The patient had an 18-month history of biopsy-proven hidradenitis suppurativa. Examination under anesthesia disclosed a 9×6 cm left perianal mass and right 5×3 cm right peri-scrotal mass; both masses were excised and revealed adenocarcinoma with signet ring cell differentiation. The patient was diagnosed with widely metastatic adenocarcinoma of unknown primary. Initiation of palliative capecitabine was planned however the patient decompensated and expired one month from the time of his diagnosis due to septic shock. Autopsy with histologic staining revealed innumerable liver lesions consistent with rare variant Intrahepatic Cholangiocarcinoma (ICC) with signet-ring cell differentiation. Multiple red papules were noted on the aortic valve with histology similarly demonstrating signet-ring cell adenocarcinoma. Cutaneous metastasis of cholangiocarcinoma has been reported but is rare, and to our knowledge this is the first reported case of cholangiocarcinoma cutaneous metastasis in a patient with hidradenitis suppurativa. This case re-emphasizes the protean presentation and aggressive metastatic potential of ICC. It also highlights the importance of maintaining a wide differential for dermatologic lesions in patients with hidradenitis suppurativa and postulates a mechanism for metastatic seeding of areas affected by this disease.